Influencia de el tipo de pustula de roya (Uromyces phaseoli (Reben) Wint.) sobre el rendimiento de cultivares de frijol (Phaseolus vulgaris L.) - Castaño Zapata, Jairo; Montoya, C.A.; Pastor Corrales, Marcial A. (1986)
Yield losses due to Uromyces phaseoli were determined in 9 bean var. selected for pustule size: BAT 93, BAT 308, and EMP 81 (type 3 pustules; more than 300 millinicrons in diameter, approx.); Jamapa, ExRico 23, and BAT 883 (type 5 pustules; more than 500 millimicrons in diameter, surrounded by a chlorotic halo), and BAT 41, BAT 527, and BAT 153 (type 3, 4, or 5 pustules). The expt. was conducted at CIAT with the following treatments: (1) naturally inoculated plots, (2) artificially inoculated plots, and (3) plots periodically protected with fungicide. Day/night av. temp. and RH during the exptl. period were 28/26 degrees C and 75/99 percent, resp., optimum conditions for rust development in beans. Var. with type 3 pustules (BAT 93, BAT 308, and EMP 81) showed the lowest areas under the curve in disease progress. Var. with type 5 pustules (Jamapa, ExRico 23, and BAT 883) showed the largest areas and var. with type 3, 4, or 5 pustules (BAT 41, BAT 527, and BAT 153) showed areas with intermediate value. In the fungicide-protected treatments, disease was not controlled in ExRico and BAT 883 (highly susceptible var.). With natural infection, small-pustuled var. yielded an av. of 334 kg/ha more than large-pustuled var. (1.5 times more). Disease control with fungicide allowed an increase of 770 kg/ha in the av. yield of large-pustuled var., equivalent to 3.4 times more than the increase in the av. yield potential of the small-pustuled var. This significant increase suggests that current yields can be increased more economically, adding resistance genes. (CIAT)